2005
DOI: 10.2987/8756-971x(2005)21[328:pcapso]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Predatory Capacity and Prey Selectivity of Nymphs of the Dragonfly Pantala Hymenaea

Abstract: Predatory capacity and prey selectivity of nymphs of the dragonfly Pantala hymenaea (Odonata: Libellulidae) were evaluated on larvae of the mosquito Culex quinquefasciatus (Diptera: Culicidae) and larvae of the midge Chironomus plumosus (Diptera: Chironomidae) as prey. With functional response methodology, 7 larval densities were exposed to predator individuals in a glass jar under laboratory conditions. The study was performed in 2 experiments. The 1st was a test system with each prey species alone. The 2nd t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…Much recent literature has focused on effects of odonates and hemipterans as predators and oviposition deterrents of mosquitoes (Arav and Blaustein 2006;Blaustein 1998;Blaustein et al 2004;Bond et al 2006;Quiroz-Martinez et al 2005;Shaalan et al 2007;Spencer et al 2002;Stav et al 1999Stav et al , 2000Yanoviak 1999Yanoviak , 2001. We found a negative, but nonsigniÞcant, trend between the density of mosquitoes and densities of Odonata and Hemiptera (linear regressions: r 2 ϭ 0.022, F 1, 178 ϭ 4.001, P ϭ 0.047, and r2 ϭ 0.041, F 1, 178 ϭ 7.581, P ϭ 0.007, respectively, critical ␣ ϭ 0.002).…”
Section: Discussionmentioning
confidence: 99%
“…Much recent literature has focused on effects of odonates and hemipterans as predators and oviposition deterrents of mosquitoes (Arav and Blaustein 2006;Blaustein 1998;Blaustein et al 2004;Bond et al 2006;Quiroz-Martinez et al 2005;Shaalan et al 2007;Spencer et al 2002;Stav et al 1999Stav et al , 2000Yanoviak 1999Yanoviak , 2001. We found a negative, but nonsigniÞcant, trend between the density of mosquitoes and densities of Odonata and Hemiptera (linear regressions: r 2 ϭ 0.022, F 1, 178 ϭ 4.001, P ϭ 0.047, and r2 ϭ 0.041, F 1, 178 ϭ 7.581, P ϭ 0.007, respectively, critical ␣ ϭ 0.002).…”
Section: Discussionmentioning
confidence: 99%
“…En tanto B. fasciata al ser un depredador que comparte el mismo hábitat de las larvas de Ae. aegypti, muestra menor efecto sobre la densidad larval relacionado probablemente con el equilibrio entomófago-presa, condicionado al consumo solo de lo necesario para satisfacer el requerimiento alimenticio evitando la extinción del recurso en control, que implica en términos biológicos eficiencia en la respuesta antidepredación de la presa y el posible ajuste coevolutivo entre ambos organismos establecido por selección natural a lo largo de cientos de miles de años, que evita la desaparición de una de las dos poblaciones (Fernández-Arhex y Corley 2004;Quiroz-Martínez et al 2005).…”
Section: Discussionunclassified
“…israelensis en el control de las larvas de los mosquitos y mejorar el efecto regulador de las poblaciones en zonas propensas a enfermedades metaxénicas. Estos diseños reducen los gastos y repercuten en la economía, no requiriendo aplicaciones repetitivas de plaguicidas químicos, sobre todo cuando se logra el establecimiento de los depredadores y patógenos en los criaderos naturales, con beneficios ecológicos de bajo impacto en los ecosistemas y en lo social, por la disminución de la casuística de las enfermedades al controlar la densidad de los mosquitos adultos transmisores (Quiroz-Martínez et al 2005;Fimia-Duarte et al 2010).…”
Section: Discussionunclassified
“…riparius ), suggesting a possible feeding preference for mosquitoes, which is in line with previous observations [ 18 ]. Other studies on feeding preference of dragonfly larvae (Pantala hymenaea) showed a slight preference for Chironomidae over Culicidae [ 39 ], indicating a possible difference between Odonata and Hemiptera species. These results thus indicate apparent competition between Chironomidae and Culicidae, which is important for potential use of predators in mosquito and mosquito-borne disease control [ 17 , 37 ], because prey specificity is an important component of biological control.…”
Section: Discussionmentioning
confidence: 99%